2019
DOI: 10.1016/j.jhealeco.2019.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The affordable care act and ambulance response times

Abstract: and Policy Studies Seminar Series for their helpful comments and suggestions. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 79 publications
2
9
1
Order By: Relevance
“…In contrast to our results, 2 previous studies by Courtemanche et al reported that ACA implementation was associated with increased EMS dispatches within the NYC EMS system. The first showed that ambulance dispatches for minor injuries increased following implementation of the ACA, and the second described an overall increase in all calls of relatively lower severity over the same time period . The authors attributed these trends to insurance expansion on the grounds that health insurance insulated patients from the costs of utilizing EMS .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our results, 2 previous studies by Courtemanche et al reported that ACA implementation was associated with increased EMS dispatches within the NYC EMS system. The first showed that ambulance dispatches for minor injuries increased following implementation of the ACA, and the second described an overall increase in all calls of relatively lower severity over the same time period . The authors attributed these trends to insurance expansion on the grounds that health insurance insulated patients from the costs of utilizing EMS .…”
Section: Discussioncontrasting
confidence: 99%
“…The first showed that ambulance dispatches for minor injuries increased following implementation of the ACA, 10 and the second described an overall increase in all calls of relatively lower severity over the same time period. 2 The authors attributed these trends to insurance expansion on the grounds that health insurance insulated patients from the costs of utilizing EMS. 10 Unlike asthma, minor injuries are not sensitive to ambulatory care, so increased access to primary care services would not have had an effect on the incidence of minor emergencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cities have noticed enough residents making this shift that they have discussed how these ride‐sharing services could be integrated into their EMS frameworks. Furthermore, the introduction of the Affordable Care Act has slowed ambulance response times by 19% (Courtemanche, Friedson, Koller, & Rees, ), exacerbating the need for a partial substitute to traditional ambulances.…”
Section: Introductionmentioning
confidence: 99%
“…5 Further understanding the effect of RT on health will also facilitate more efficient healthcare policies. An example is the improvement in access to ambulance services as a result of the Affordable Care Act in the US, which resulted in a 19% increase in wait times due to the increased strain on the system (Courtemanche et al, 2019).…”
mentioning
confidence: 99%